Pengembangan Usaha Lampu Hias Pipa Mg Craft Melalui Kegiatan Pengabdian Kepada Masyarakat Universitas Prasetiya Mulya - Ramadhan, Achmad Rifqi; Sutjiadi, Hansen; Anggie, Hendry; Paseru, Reydia Adriel; Yul, Selly; Katrina, Sonya; Yenchristie, Stephanie; Agustiawan, Sonny (Journal Pemberdayaan Masyarakat Indonesia, 2019)
Community Development is a lecture activity held by Prasetiya Mulya University for semester 5 students. On this occasion our group obtained business partners in the Wangunjaya Village, Cugenang District. Who owns the business consists of decorative lights which have raw materials consisting of paralon pipes made of PVC (Polyvinyl Chloride). Starting from the operational aspects, financial, human resources to marketing. The target that our group have discussed is to expand the scope of this business, so that the number of people who know this product and its development can increase significantly. In terms of operations, our partner have been able to produce up to 100 products per month after occupying a new place. Before he moved to the new place, our partner was only able to produce 50 products per month. For finance, our partner use Value-Based Pricing strategies to determine the selling price of each product. In addition, we also managed to increase our partner's monthly income from Rp 2.375.000,- to Rp 4.257.300,-. Then, for the marketing department, our group had suggested our partner to uses social media like Instagram to market our products. Instagram is used to promote existing products, while more information about products and special orders can be done via WhatsApp. And for the human resources section, our partners managed to increase the number of employees from 2 employees to 5 employees